Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019 Proceedings of the Twenty-First Workshop on Algorithm Engineering and Experiments (ALENEX) 2019
DOI: 10.1137/1.9781611975499.11
|View full text |Cite
|
Sign up to set email alerts
|

Efficiently Enumerating Hitting Sets of Hypergraphs Arising in Data Profiling

Abstract: We devise an enumeration method for inclusion-wise minimal hitting sets in hypergraphs. It has delay O(m k * +1 • n 2 ) and uses linear space. Hereby, n is the number of vertices, m the number of hyperedges, and k * the rank of the transversal hypergraph. In particular, on classes of hypergraphs for which the cardinality k * of the largest minimal hitting set is bounded, the delay is polynomial. The algorithm solves the extension problem for minimal hitting sets as a subroutine. We show that the extension prob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…Indeed, the particular case α = 2 of MMHS corresponds to the Maximum Minimal Vertex Cover (MMVC for short) problem, which is NP-hard [7]. When parameterizing by β only, we show in Proposition 6 that MMBS is para-NP-hard, whereas MMHS is W [1]-hard [2] and XP [4]. As discussed in Section 3, the W [1]-hardness proof of [2] implies that, unless the Exponential Time Hypothesis (ETH for short) fails, Up-Dom cannot be solved in time f (k) • n o( √ k) on n-vertex graphs for any computable function f .…”
Section: Contribution and Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, the particular case α = 2 of MMHS corresponds to the Maximum Minimal Vertex Cover (MMVC for short) problem, which is NP-hard [7]. When parameterizing by β only, we show in Proposition 6 that MMBS is para-NP-hard, whereas MMHS is W [1]-hard [2] and XP [4]. As discussed in Section 3, the W [1]-hardness proof of [2] implies that, unless the Exponential Time Hypothesis (ETH for short) fails, Up-Dom cannot be solved in time f (k) • n o( √ k) on n-vertex graphs for any computable function f .…”
Section: Contribution and Related Workmentioning
confidence: 99%
“…Finally, when parameterizing by α + β, the hardness result given in Proposition 6 (i.e., parameterizing by α for fixed β) implies that MMBS is W [1]-hard, whereas MMHS is FPT for the following reasons. We first provide in Corollary 18 a simple FPT algorithm for MMHS that reduces to an extension problem considered by Bläsius et al [4], and then design in Theorem 24 a more involved an ad-hoc algorithm to improve the running time to O * (2 αβ ), where the O * -notation hides multiplicative polynomial terms (see Section 2).…”
Section: Contribution and Related Workmentioning
confidence: 99%
“…In fact, enumeration algorithms are often analyzed not only with respect to their running time, but also in terms of space consumption, see [9,14]. For data profiling problems like Enumerate Minimal UCCs on the other hand, space-efficient algorithms have only recently started to received some attention [5,6,36].…”
Section: Approximation and Discoverymentioning
confidence: 99%
“…We show here that the detection of inclusion dependencies has this property, making it the second such problem. Since this result was first announced, Bläsius et al [6] have also proven the extension problem for minimal hitting sets to be W[3]-complete using different techniques. The latter has subsequently been improved by Casel et al [11], they have shown that already the special case of extension to minimal dominating sets in bipartite graphs is hard for W [3].…”
Section: Introductionmentioning
confidence: 99%
“…The following fundamental combinatorial optimization problem arises in bioinformatics [43], medicine [41,51], clustering [12,36], automatic reasoning [16,25,48], feature selection [15,30], radio frequency allocation [49], software engineering [47], and public transport optimization [14,52].…”
Section: Introductionmentioning
confidence: 99%